Comparative study of two different techniques for leak and bleeding prevention during laparoscopic sleeve gastrectomy - Mukhtar, Ramiz S. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Laparoscopic sleeve gastrectomy has gained more popularity as an independent bariatric procedure because laparoscopic sleeve gastrectomy was reported to be an effective, safe, and time-savingprocedure, leading to adequate weight loss for morbidly obese patients and becoming one of the most common procedures performed for the treatment of morbidly obese patients in the last few years until now.Objectives: The aim of this study is to compare two different techniques of the reinforcement of staple line during LSG in the reduction of major complications (bleeding and leak).Patients and methods: prospective randomized study of a consecutive series of 126 patients that underwent LSG between April 2014 till August 2015. Patients were randomly enrolled in two different techniques of reinforcing the staple line during LSG, Group A consisted of 63 patients that underwent sleeve gastrectomy using Ethicon Endo GIA stapleTM with staple line oversewn using 2.0 prolene continuous suture, group B also 63 patients who had the staple-line oversewn with a continuous suture using V-locTM and Covidien Endo GIA tristapleTM.Results: 126 patients who underwent LSG, 82(65%) were women and 44(35%) were men. Median age was 36 years (range, 19–58 years) and median preoperative BMI was 45.4 kg/m2 (range, 37–62 kg/m2), Three patients (4.76%)from group (A) and 2 patients (3.17%)from group (B)developed primary hemorrhage (within the first 24 hours post operatively), overall bleeding rate in both groups was (3.96%), no leak in both groups and no mortality.Conclusion: laparoscopic sleeve gastrectomy is a safe procedure as a sole weight reduction operation. The combination of meticulous surgical technique, reinforcement of the gastric staple line, lead to decrease the incidence of staple line leak whatever the suture material or stapler type used, but there is no significant decrease in the incidence of bleeding with staple line reinforcement.